Findings of living donation experiences shared on a digital storytelling platform: A thematic analysis - Erica W. Ho; Ariana L. Murillo; LaShara A. Davis; Yaquelin Arevalo Iraheta; Shailesh M. Advani; Ashley Feinsinger; Amy D. Waterman (PEC Innovation, 2022)
Objectives: To identify common experiences and emotional changes shared by living donors and kidney recipients about their living donation experiences on a digital storytelling platform. Methods: 82 donors and 36 recipients submitted prompt-guided videos to the platform. Two coders analyzed transcripts for motivations, common themes, and emotions expressed. Results: Storytellers shared their stories to advocate for living donation and contribute to others facing similar challenges. Pre-surgery, recipients recalled their dialysis experiences and how they sought living donors while donors discussed their motivations and common fears. Post-surgery, recipients discussed changes in their relationship with the donor and quality life, while donors described how they benefited. Learning they needed a transplant, recipients reported feeling fear (33.3%) while donors felt sadness (48.8%). Post-transplant, recipients and donors reported feeling happiness (85.4%, 38.9%) and relief (29.3%, 22.2%). Conclusion: Online digital storytelling libraries increase access to real-life living donation experiences. Since stories are highly personal, additional living donor kidney transplant risk-benefit education is needed. Innovation: Stories can supplement traditional education and be incorporated into advocacy efforts; campaigns could capitalize upon the personal aspect of stories to gently introduce and encourage living kidney donation among the general public.